An analysis on the importance of motivation to transfer learning in VUCA environments - Christian Haposan Pangaribuan (Management Science Letters, 2020)
In this VUCA world, much can be achieved when one is open to learning. The purpose of this study is to ana-lyze the impact of organizational learning culture, employee commitment, and job satisfaction towards motivation to transfer learning. The data are collected by distributing 200 questionnaires for employees working in Jakarta area. The method used to do the analysis is by using a multilinear regression. Based on the result, organizational learning culture and job satisfaction had significant impacts to motivation to transfer learning. Meanwhile, employee commitment does not have significant effect on motivation to transfer learning, however, it has an impact on the gender, age, and length of work.